Behaviorism Psychology Approach in Quranic Studies - Khusnul Khotim; Qorin Karim; Maharani Wulandari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The main purpose of the Qur'an is to improve human morals. The appropriate scientific discipline to study human behavior in psychology. Unfortunately, the psychological approach in Qur'anic studies is still rarely used. This paper aims to provide a building method of researching the Qur'an with a psychological approach, especially behaviorism which is the earliest approach of psychology. This research method uses a qualitative method with the type of library research. In the process of collecting data, researchers use the documentation method, which is the search for data related to variables or things in the form of books, journals, etc. The result of this study shows that In the behaviorist psychological approach, it is necessary to determine the dependent variable (which is affected) and the independent variable (which affects). In the context of Qur'anic studies, human interaction with the Qur'an can be the independent variable, while certain behaviors can be the dependent variable. Vice versa, human behavior can be an independent variable that affects human interaction with the Qur'an as the dependent variable. Research can also be conducted by observing objects as they are (natural) or observing objects in an artificial environment (experimental). The recommendation for further research is to promote Quranic research with a behaviorist approach. Other research models that try to make the Qur'an practical need to be encouraged, so that the ideals of the Qur'an to be able to influence human ethics can be achieved.